Spanje herdenking met Piet Laros in het midden, links mevr. Van Reemst-de Vries en rechts mevr. Van Bergen-Diamant
Spanje herdenking met Piet Laros in het midden, links mevr. Van Reemst-de Vries en rechts mevr. Van Bergen-Diamant.